The other side of dawn - Marsden, John, 1950- (New York Scholastic Inc., 2002)
Ellie and her friends, five Australian teenagers who survived the enemy invasion of their country, use guerrilla tactics to support a major counterattack by New Zealand troops.
Series statement on jacket.
Keywords: Survival -- Fiction; War stories; Australia -- Fiction; Young adult fiction